The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s1413-77392000000100005
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de idades e crescimento do linguado branco Paralichthys patagonicus (Jordan, 1889) no sul do Brasil

Abstract: A idade e o crescimento do linguado-branco Paralichthys patagonicus (Jordan, 1889) foram estudados a partir de amostras obtidas da pesca comercial no sul do Brasil entre 1989 e 1991. As idades foram determinadas sobre cortes transversais de otólitos de 460 exemplares. A análise do tipo de bordo e dos incrementos marginais dos otólitos mostrou que, a cada ano ocorre a formação de uma zona translúcida e uma zona opaca nos otólitos. As "remeas atingem maiores tamanhos e idades (630 mm, 13 anos) do que os machos (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
(8 reference statements)
0
6
0
2
Order By: Relevance
“…Theoretical growth in weight was estimated by transforming length-at-age data into weight-at-age data based on the potential weight-length equations. Calculations of absolute weight gain were based on the differences among mean theoretical weights at consecutive ages (Araújo and Haimovici, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical growth in weight was estimated by transforming length-at-age data into weight-at-age data based on the potential weight-length equations. Calculations of absolute weight gain were based on the differences among mean theoretical weights at consecutive ages (Araújo and Haimovici, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The difference in body length between males and females is related to variation in growth parameters (Morita et al, 2015). From the adaptive point of view, this variation allows greater fecundity per unit biomass, since larger females can produce more eggs (Costa, Mateus, 2009), or the production of larger eggs with greater food reserves and thus the promotion of enhanced larval survival rates (Stearns, 1976;Araújo, Haimovici, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition it is important to consider the sex of the individual, since the occurrence of sexual dimorphism is common in both marine and freshwater fish. Consideration of the influence of differences in behaviour and differential investment in reproduction and growth between the sexes has permitted a better understanding of autoecology and dynamics of fish stocks (Araújo, Haimovici, 2000). Studies investigating the role of sex as a factor in growth models and methods for back-calculating size have shown that much of the variation between individuals is related to sex (Kielbassa et al, 2011;Ambrósio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A mortalidade natural engloba diversas causas como condições abióticas adversas, falta de alimento, doença, senilidade e predação (Ricker, 1975). A taxa instantânea de mortalidade natural, M foi estimada pelo método de Alagaraja (1984) (Araújo & Haimovici, 2000).…”
Section: Methodsunclassified
“…As idades podem ser determinadas sobre os otólitos. As fêmeas são mais longevas e atingem maiores tamanhos que os machos (Araújo & Haimovici, 2000).…”
unclassified